Pengaruh Motivasi Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan Head Office PT Nojorono Tobacco International - Simamora, Arnade Immanuel; Hermana, Cecep (Peneliti.net, 2023)
This study aims to determine, analyze and explain the influence of work motivation and work discipline on the performance of Head Office employees of PT. Nojorono Tobacco International. This research uses descriptive and verification research methods with quantitative research types. The population of this research is Head Office employees of PT. Nojorono Tobacco International, with a total of 201 employees and a sample of 138 respondents who were calculated using the solvency formula at a level of 5%. While the sampling technique in this study used a simple random sampling technique. The results showed that there was a partial influence between work motivation and work discipline on the performance of employees at PT Nojorono Tobacco International. The magnitude of the influence of work motivation on employee performance is 29%. Meanwhile, the magnitude of the influence of work discipline on employee performance is 30.2%. There is a simultaneous influence between work motivation and work discipline on the performance of employees of PT Nojorono Tobacco International. the total effect caused by work motivation and work discipline variables on employee performance is 59.2%. while the influence of other variables outside the research model is 40.8%.